Patients’ expectations of private osteopathic care in the UK: a national survey of patients - Leach, CM Janine (BioMed Central, 2013)
BACKGROUND: Patients’ expectations of osteopathic care have been little researched. The aim of this study was to quantify the most important expectations of patients in private UK osteopathic practices, and the extent to which those expectations were met or unmet. METHODS: The study involved development and application of a questionnaire about patients’ expectations of osteopathic care. The questionnaire drew on an extensive review of the literature and the findings of a prior qualitative study involving focus groups exploring the expectations of osteopathic patients. A questionnaire survey of osteopathic patients in the UK was then conducted. Patients were recruited from a random sample of 800 registered osteopaths in private practice across the UK. Patients were asked to complete the questionnaire which asked about 51 aspects of expectation, and post it to the researchers for analysis. The main outcome measures were the patients-perceived level of expectation as assessed by the percentage of positive responses for each aspect of expectation, and unmet expectation as computed from the proportion responding that their expectation “did not happen”. RESULTS: 1649 sets of patient data were included in the analysis. Thirty five (69%) of the 51 aspects of expectation were prevalent, with listening, respect and information-giving ranking highest. Only 11 expectations were unmet, the most often unmet were to be made aware that there was a complaints procedure, to find it difficult to pay for osteopathic treatment, and perceiving a lack of communication between the osteopath and their GP. CONCLUSIONS: The findings reflected the complexity of providing osteopathic care and meeting patients’ expectations. The results provided a generally positive message about private osteopathic practice. The study identified certain gaps between expectations and delivery of care, which can be used to improve the quality of care. The questionnaire is a resource for future research.